Effective bounds of the variance of statistics on multisets of necklaces - Karbonskis, Arvydas; Manstavičius, Eugenijus (Lietuvos matematikos rinkinys, 2021)
The variance of a linear statistics on multisets of necklaces is explored. The upper and lower bounds with optimal constants are obtained